Comparison between the Effectiveness of Tomatoes Juice and Spinach Juice Consumption on Hemoglobin Level of Third Trimester Mothers with Anemia - Retno Widowati; Nurhasanah Nurhasanah; Bunga Tiara Carolin (Universitas STRADA Indonesia, 2021)
The current research was conducted through a quasi-experimental research using two group pretest-posttest design. Furthermore, data analysis was done by using dependent t-test and independent t-test. As many as 30 pregnant mother suffering from anemia were involved and divided into two groups. The first group consumed tomatoes juice, while the second group consumed spinach juice every day for 14 days. All mothers also consumed Fe tablet every day according to the regulation. This research was carried out in Tangerang District on January 2021. These research results revealed that there was significant differences on the hemoglobin level before and after tomatoes juice and spinach juice consumption on the experimental groups. Significant differences on hemoglobin level were also found between the effectiveness of tomatoes juice and spinach juice on trimester pregnant mothers suffering from anemia (p value 0.037).